AN ANALYSIS OF THE APPLICATION END TO END QUALITY OF SERVICE ON 3G TELECOMMUNICATION NETWORK - Lukito, Cahya; Lukito, Rony Baskoro; Arifin, Deddy (CommIT (Communication and Information Technology) Journal, 2012)
End to End Quality of Service is a way to provide data package service in a telecommunication network that based on Right Price, Right Service Level, and Right Quality. The goal of this research is to analyze the impact of End to End QoS use on 3G telecommunication network for voice service and data. This research uses an analysis method by doing the application on the lab. The result that is achieved in this research shows that End to End QoS is very influental to the Service Level Agreement to the users of the telecommunication service.Keywords: End to End Qos, SLA, Diffserv